Kesantunan Berbahasa dalam Novel Suluh Rindu Karya Habiburrahman El Shirazy - Andi Dhea Namirah; Usman Usman; Aswati Asri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research is a qualitative descriptive study which aims to describe and analyze politeness in language between characters and then describe the problem as a meaning or new information through the Maxims of content in the Novel Suluh Rindu. The data source for this research is to know the contents of the Novel Suluh Rindu, namely there are 6, then the data collection technique in this research uses reading techniques and note-taking techniques. The data analysis techniques in this research are data reduction, data presentation, and drawing conclusions. The results of this research show 1) The wisdom Maxim (tax Maxim) 2) Generosity Maxim 3) Approbation Maxim contained 4) The Modesty Maxim 5) The sympathy Maxim contained in the novel Suluh Miss by Habiburrahman El Shirazy means that in this 6) The Maxim of Agreement (agremeent Maxim) contained in the novel suluh longing by Habiburrahman El Shirazy means that in this novel it functions as a reminder of the importance of tolerance and respect for differences of opinion. By agreeing with other people's opinions and beliefs, we can show that we respect them.